2022
DOI: 10.1210/jendso/bvac144
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalized Patients With COVID-19 Have Higher Plasma Aldosterone-Renin Ratio and Lower ACE Activity Than Controls

Abstract: Background SARS-CoV-2 infects cells via the ACE2 receptor, whose downstream effects “counterbalance” the classical renin angiotensin aldosterone system (RAAS). It is uncertain to what extent circulating RAAS biomarker levels differ in persons with and throughout COVID-19. Methods We measured classical (renin, aldosterone, aldosterone/renin ratio [ARR], Ang2, ACE activity, ) and nonclassical (ACE2, Ang1,7) RAAS biomarkers in h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Similar sACE activity in COVID-19-induced ARDS and non-ARDS patients [236]. sACE activity was lower in patients with COVID-19 vs. controls [245,246].…”
Section: Plasminogenmentioning
confidence: 69%
See 1 more Smart Citation
“…Similar sACE activity in COVID-19-induced ARDS and non-ARDS patients [236]. sACE activity was lower in patients with COVID-19 vs. controls [245,246].…”
Section: Plasminogenmentioning
confidence: 69%
“…The respective activities, however, increased in the recovery phase, and the authors concluded that serum ACE activity could be potentially used as a marker reflecting COVID-19 severity, since low activity was associated with the severity of COVID-19 at baseline, and the activity increased with the remission of the disease [244]. Likewise, others have shown that serum ACE activity was lower in patients with COVID-19 vs. controls [245,246]. In another study, serum ACE activity upon hospital admission did not reflect disease severity [247], while our group demonstrated that serum ACE activity was similar in COVID-19 ARDS and non-ARDS patients [236].…”
Section: Renin-angiotensin-aldosterone System (Raas)mentioning
confidence: 97%